Scientific Foundations of Water Requirements of Peanuts in the Conditions of the Central Region of Uzbekistan - Khudaykulov, J. B.; Tajetdinov, N. D.; Saparbaev, Z. Y. (American Journal of Botany and Bioengineering, 2025)
Scientific research on ecological testing and selection of peanut varieties in various soil and climatic conditions, increasing yield and seed quality, and improving cultivation technology has been conducted at leading international scientific centers and higher educational institutions around the world. In this article presented data obtained during the study of water requirements of peanut varieties at the central region of Uzbekistan. The increase in the number and rate of irrigation of peanuts has a positive effect on the acceleration of its physiological processes and the extension of the growing season. When irrigation in the "Mumtoz" variety was carried out in the order of 70-75-65% compared to LFMC, the ripening period was extended by 7-10 days and amounted to 165-167 days.